Odontomas in Frogs. Issue 1 (January 2020) - LaDouceur, Elise E. B.; Hauck, Amanda M.; Garner, Michael M.; Cartoceti, Andrew N.; Murphy, Brian G.
Odontomas are variably differentiated, hamartoma-like proliferations of odontogenic epithelium, pulp ectomesenchyme (odontoblasts), and dental matrix. Frogs are polyphyodont and homodont. Their teeth also differ from mammals in that they are restricted to the upper jaw in adults and lack a periodontal ligament and cementum, attaching directly to the underlying bone. Odontomas were identified in an African clawed frog ( Xenopus laevis ), a false tomato frog ( Dyscophus guineti ), and a tomato frog of unknown species ( Dyscophus sp. ). All of the examined odontomas were composed of numerous tooth-like structures comprising an arc of dentinal matrix lined on the convex surface by ameloblasts and on the concave surface by odontoblasts. Masson's trichrome and immunohistochemistry with pan-cytokeratin supported these findings. The pathogenesis of these lesions may be displacement of the dental lamina, which has been shown in research studies to lead to de novo proliferation of dental elements in frogs.